Pengaruh Pemanfaatan Augmented Reality dan Motivasi Belajar Siswa terhadap Hasil Belajar Matematika Siswa Kelas V SD Kumnamu Tangerang - Marisa, Riandi; Ana Maharani Keban; Gusti Yarmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The advancement of digital technology necessitates innovation in the learning process, one of which involves the utilization of Augmented Reality (AR) as an interactive learning medium. This research aims to investigate the influence of Augmented Reality utilization on students' mathematics learning motivation and outcomes in Class V of SD Kummaru Tangerang, employing both partial and simultaneous approaches. This quantitative research employs the Augmented Reality learning method, with a total sample of Class V students from SD Kummaru Tangerang, comprising 34 students, subdivided into respondents. Data collection was conducted using questionnaires and documentation, followed by descriptive analysis employing SPSS version 26. The analytical techniques employed include validity and reliability tests, normality tests, multicollinearity tests, correlation tests, and linear regression. The research findings demonstrate that the Augmented Reality variable exerts a significant positive influence on students' mathematics learning motivation. Students' learning motivation also demonstrates a significant positive influence on mathematics learning outcomes. Furthermore, the regression test results indicate that the implementation of Augmented Reality and learning motivation simultaneously provide a significant contribution to mathematics learning outcomes, accounting for a determinant contribution of 59.7%. Consequently, it can be concluded that enhancing students' mathematics learning outcomes must consider the important role of Augmented Reality media and learning motivation. This research provides an alternative strategy for improving the quality of mathematics education in elementary schools.